2020
DOI: 10.2147/oas.s285562
|View full text |Cite
|
Sign up to set email alerts
|

<p>Preoperative Anxiety and Associated Factors Among Adult Elective Surgery Patients in North Wollo Zone, Northeast Ethiopia</p>

Abstract: Background: Higher levels of preoperative anxiety may be associated with life-threatening postoperative complications and increase the risk of postoperative mortality. Therefore, this study aimed to assess the prevalence and associated factors of high level of preoperative anxiety among elective surgical patients in North Wollo Zone, Northeast, Ethiopia. Methods: Hospital-based, cross-sectional study was conducted on 211 patients scheduled for surgery. Participants were selected using a systematic random sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…The finding of this study is comparable with the study done in Ethiopia (Wollo 48.3%), 25 Nigeria (51%), 19 whereas lower when compared to the study done in America (72.7%), 15 Norway, 32 Nepal (70.6%), 10 Rumand (72.8%), 21 and Ethiopia (Gonder (59.6%), Debre Markos (61%) and Jimma (70.3%)). 11 , 13 , 24 The variation might be due to the variation in study participants; for instance, in studies done in America, the participants were only female, which increases the prevalence.…”
Section: Discussionsupporting
confidence: 82%
“…The finding of this study is comparable with the study done in Ethiopia (Wollo 48.3%), 25 Nigeria (51%), 19 whereas lower when compared to the study done in America (72.7%), 15 Norway, 32 Nepal (70.6%), 10 Rumand (72.8%), 21 and Ethiopia (Gonder (59.6%), Debre Markos (61%) and Jimma (70.3%)). 11 , 13 , 24 The variation might be due to the variation in study participants; for instance, in studies done in America, the participants were only female, which increases the prevalence.…”
Section: Discussionsupporting
confidence: 82%
“…Patients need to be assessed regularly for anxiety during the preoperative visit (Bedaso & Ayalew, 2019). in conjunction with the study of Wondmieneh A et al also found that fear of death, fear of the unknown, and fear of postoperative complications were significant predictors of the emergence of preoperative anxiety (Wondmieneh, 2020).…”
Section: Factors Influencing Anxiety In Patients Before Cardiac Surgerymentioning
confidence: 99%
“…For this purpose, a single population formula was used to obtain a final sample size of 423 with an assumption of 0.05 margin of error(d), a 95% confidence interval (CI), and a 48.3% estimated proportion of POA (P) taken from a study conducted in Wollo, Northeast Ethiopia. 23 A systematic random sampling technique was employed to select a total of 423 study participants. The average number of participants in four public hospitals was estimated from last year's monthly reports (Howot Fana Comprehensive Specialized University Hospital (HFCSH) (300), Jugula Hospital (JH) (180), Dire Dawa Referral Hospital (DRH) (235), and Sabian General Hospital (SGH) (155)) before data collection.…”
Section: Sample Size Determination and Sampling Proceduresmentioning
confidence: 99%
“…Ten statements in the state section of the STAI (Y-1) show anxiety (items 3, 4, 6, 7, 9, 12, 13, 14, 17, and 18), whereas the remaining ten statements (items 1, 2, 5, 8, 10, 11, 15, 16, 19, and 20) represent the patient's relaxed and pleasant mood. 23 For the ten positive S-Anxiety items, a score of four indicates the existence of extreme anxiety, whereas a high grade indicates the lack of anxiety for the remaining 10 negative items for anxiety.…”
Section: Variables and Measurementsmentioning
confidence: 99%